LABORATORY INVESTIGATION ON THE CORRELATION BETWEEN THE FRICTION ANGLE OF ROCK JOINTS AND THE CONSTANT MI OF THE HOEK AND BROWN CRITERION - Tsikrikis, A.; Papaliangas, T.; Marinos, V. (Bulletin of the Geological Society of Greece, 2016)
A correlation between the non-dilational friction angle (φm) of rock discontinuities and the constant mi of the Hoek and Brown criterion for intact rock is investigated, using the results of a focus oriented laboratory program. The program consisted of two types of laboratory tests: a series of triaxial compression tests on intact rock samples for the determination of the constant mi and an independent series of direct shear tests on tensile fractures of the same rock types for the determination of the rock joint friction angle φm. Four typical rock types from Northern Greece were used: a granite, a sandstone, a limestone and a marble, covering a range of mi between 8 and 34, and an unconfined compressive strength between 60 and 120 MPa. Apart from the certain range of parameters that is presented for this specific rocks, the experimental results show that the non-dilational friction angle of the rock fracture determined by direct shear testing (φm) decreases logarithmically with the value of the constant mi.